Sistem Digitalisasi Arsip Berbasis Web Menggunakan Framework Bootstrap Dengan Metode Prototype (Studi Kasus: CV. Munding Laya Jaya) - Rio Putra Pratama, Slamet; Munaldi (CV. Shofanah Media Berkah, 2023)
The development itself is inseparable from the human need for fast and accurate information. All kinds of information and management that are currently managed by institutions strongly support the development of systems that rely on technological advances. One of them is the field of information technology and data processing. CV. Munding Laya Jaya is one of the offices engaged in law and legislation to create certainty, order and legal protection. Many deeds on CV. Munding Laya Jaya. The process of filing records is still done manually and stored in the filing cabinet. After the archive enters, it is stored in the filing cabinet according to the sequence number. Then if employees want to search for the old files they need, they have to look at the files in the filing cabinet one by one, so it takes a long time to find the files needed. Responding to these problems, the author proposes to build an archive digitization system using the PHP programming language with the framework is bootstrap and using the Prototype method for the development of the system to be used. With this Prototype method, it can collect user needs for the software to be created and then a Prototype program is made so that users better understand what they want, the program is then evaluated by the user until the specifications are found that match their wishes. This website was created to help employees find archive information more easily and neatly stored in a web application.